Supporting Local SMEs through the Digitalization of Ecotourism Village Business in South Tangerang - Abdul Haris Muchtar; Sujoko Winanto; Zulfikar Said Agil Sidiki; Arsa Samrotul Fuadah; Aulia Islami Ansar; Eldrian Addin Naufal; Hana Hanifah; Khayla Qalisya; Sayyidah Aisyah Al-Humairah Ahmad; Muhammad Fauzan (SocietalServe: Journal of Community Engagement and Services, 2024)
The COVID-19 pandemic has had a significant impact on the economic sector, particularly MSMEs, which have struggled to adapt to the digital era. This report discusses the implementation of a community empowerment program aimed at enhancing MSMEs' ability to utilize digital marketing through social media platforms such as Instagram and Facebook. The program involved stages of FGD, surveys, socialization, training, mentoring, and evaluation. The culminating activity, a webinar titled "Optimizing Your Instagram for Business," was attended by 10 MSMEs. Evaluation results showed that the program successfully improved participants' understanding and skills in utilizing social media to boost sales. It is hoped that similar programs can continue to support MSMEs in facing the challenges of the digital era and increase their contribution to the national economy.